PP-30 Clinical utility and safety of ganoderma lucidum extract in acute lymphoblastic leukaemia as a adjuvant therapy: a case report. Issue 10 (20th September 2017) - Peire,; Ana, Fernandez de; Luces, Sanchez; Blanco, Rodriguez; Simon,
Abstract : Introduction: Acute Lymphoblastic Leukaemia (ALL) is the most common childhood malignancy. Optimal util-isation of chemotherapy in addition with supportive care achieves highest survival rates (about 85%) for children. The main problem is the drug toxicity (mostly myelosup-pression, mucositis, and nausea/vomiting) as well as re-current infections. Complementary and Alternative Medicines (CAM) are often used in Paediatric Oncology. The medicinal mush-room Ganoderma lucidum plays a pivotal role as im-mune-modulator. Medicinal mushrooms are boosters or restoring agents of the ability of the immune system to fight infections, cancer and other diseases. The main bio-active compounds in Ganoderma lucidum are polysac-charides, in the form of beta-d-glucans, and triterpenes, both with well-defined biological properties. Beta-d-glucans have demonstrated antitumor and im-mune-stimulating activities. They modulate both innate and adaptive immune responses and increase opsonic and non opsonic phagocitosis, enhancing antitumor cytotoxicity. They also induce natural killer (NK) cell cy-totoxicity against various cancer. Triterpenes are able to inhibit cancer cell growth and activity as we showed in previous experients using different cancer cell lines.This mushroom also increases plasma antioxidant capacity and enhances immune response in cancer Aim: Chemotherapy is a cause for neutropenia, increas-ing therefore the susceptibility to infections. Ganoderma lucidum previously showed to increase lymphoprolifer-ative responses in immunocompromized children with cancers in a randomised, double-blind and placebo-con-trolled study. However, clinical evidence supporting the use of medicinal mushrooms in paediatric patients is still scarce. Therefore, we decided to investigate the role of this mushroom in improving the quality of life, prevent-ing recurrences and infections in patients affected by ALL. Prior to any use the product developed, based on Local strains from Ganoderma lucidum, showed no inter-ference with the hepatic cytochromes, as we showed in previous studies Case study: A 4 year old boy with confirmed diagnose of ALL type B without leucocitosis finished his chemothera-py treatment 2 years after the initial diagnose date, with a complete remission. The patient followed the protocol 58 081 of the EORTC with good response. After getting the Informed Consent from their parents, and estimate the initial dose based on BW (mg/Kg), the child received an oral dose of 445 mg of Ganoderma lucidum powder (Bioganoderma ©) daily with excellent tolerance. Six months later, we decided to double the dose with ex-cellent clinical response as well as tolerability. Two years later, daily providing the same oral dose, the patient still was free from infection (the neutropenia was corrected), no recurrence of his malignancy) or side effects referred. Blood tests are absolutely normal, as well as the myelo-gram. In fact, currently he follows a complete normal life (school, outdoors activities). He does not have any neurological or hepatic con-sequences from this treatment. His parents referred an impressive improving in his performance status since the child has being taking this mushroom compound, Ganoderma lucidum. Conclusions: We need novel therapeutic approaches for Paediatric Cancer in order to improve the quality of life, prevent consequences and recurrences. As for adults, Ganoderma lucidum is an excellent opportunity for pae-diatric patients due to its safety, tolerability and clinical response.